Factorial validity and reliability of the General Health Questionnaire (GHQ-12) in the Brazilian physician population Questionário de Saúde Geral (QSG-12) na população médica Brasileira: evidências de validade fatorial e consistência interna - Valdiney V. Gouveia; Genário Alves Barbosa; Edson de Oliveira Andrade; Mauro Brandão Carneiro (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The 12-item General Health Questionnaire (GHQ-12) is a widely used screening instrument. One- and two-factor structures have been identified in some countries. In Brazil, the best factor structure is still unclear. This study aimed at knowing its factorial validity and reliability, and testing the one-factor and two-factor models. The participants were 7,512 Brazilian physicians. They answered the GHQ-12 and demographic questions. Unrotated (one-factor) and rotated (two-factor) structures of the GHQ-12 were extracted by principal component analysis. Confirmatory factor analyses (ML) were used to compare the one- and two-factor solutions. The two-factor model fitted the data better than the one-factor one. Those two factors were depression and social dysfunction, and they showed themselves to be directly correlated to one another. They also showed adequate reliability coefficients. The two-factor model is remarkably adequate, showing better fit indices, although it is acceptable to admit a common factor, which could be defined as psychological distress. O Questionário de Saúde Geral de 12 Itens (QSG-12) é um instrumento de triagem amplamente usado. As estruturas com um e dois fatores têm sido observadas em alguns países. No Brasil não é ainda clara a melhor estrutura fatorial. Este estudo objetivou conhecer evidências de sua validade fatorial e consistência interna. Os participantes deste estudo foram 7.512 médicos brasileiros, que responderam o QSG-12 e perguntas demográficas. Foram extraídas estruturas fatoriais rotadas (unifatorial) e não-rotadas (bifatorial) por meio de análise de componentes principais. Realizaram-se análises fatoriais confirmatórias (ML) para comparar as soluções uni e bi-fatorial. O modelo com dois fatores se ajustou melhor aos dados do que o unifatorial. Os dois fatores foram depressão e disfunção social, sendo diretamente correlacionados entre si; ambos apresentaram coeficientes de confiabilidade aceitáveis. O modelo bifatorial foi claramente adequado, apresentando os melhores indicadores de ajuste, embora possa ser aceito um fator comum, concebido como desconforto psicológico.